Pelaksanaan Administrasi Surat Menyurat dan Kearsipan di Lembaga Pendidikan - Rahayu, Putri; Tantri, Arya; Julia, Ayu Putri; Pamungkas, Faturrahman Hendli (Yayasan Daarul Huda Kruengmane, 2024)
Administration is often defined as all activities related to administration or government. Correspondence administration means the overall process of correspondence activities such as taking notes or writing, as well as organizing in the smallest matters from determining goals to implementing them so that a previously determined goal is achieved. Correspondence is an activity of conveying information from one institution to another institution. The aim of writing this article is to find out about the implementation and management of correspondence and archives administration in schools or other institutions. The method used in this article is a literature review which is carried out by collecting data or the results of scientific writing that connects research with existing literature and is used as problem solving. The method for collecting library data is by reading, taking notes and processing research data and then concluding as research material. The research results obtained explain the implementation of correspondence and archival administration.